Development of a potential vaccine against Capripox virus implementing reverse vaccinology and pan-genomic immunoinformatics. - Md Mohaimenul Islam Tareq; Sattyajit Biswas; Farazi Abinash Rahman; Labib Sharirar Siam; Sadia Jannat Tauhida; Shamim Ahmed; Hasan Jafre Shovon; Mariya Ahmed; Kazi Afrin Jerin; Md Nazmul Hasan (PLoS ONE)
CPXV is responsible for animal diseases affecting cattle (Lumpy Skin Disease), sheep (Sheeppox), and goats (Goatpox). During outbreaks, these diseases have huge socio-economic effects. Now, no vaccination that is effective against sheeppox, goatpox, and lumpy skin disease is available. This work used an immunoinformatic methodology to discover possible targets for vaccination against CPXV. After the 122 CPXV proteins were obtained from the Vipr database, several investigations into the proteins' virulence, antigenicity, toxicity, solubility, and IFN-g activity were carried out. Three outer membrane and extracellular proteins were selected to predict their B-cell and T-cell epitopes based on certain distinctive features. These epitopes exhibit conservation across three species, namely Sheeppox virus (SPPV), Goatpox virus (GTPV), and Lumpy skin disease virus (LSDV) of CPXV. This will provide more comprehensive immunity against diverse virus strains worldwide. Nine MHC-I, MHC-II, and B-cell epitopes were selected to generate multi-epitope vaccine constructions. These constructs were linked using AAY, GPGPG, and KK linkers and 50S ribosomal protein L7/L12 adjuvants to enhance the immunogenicity of the vaccines. Molecular modeling and structural validation enabled the production of vaccine constructs with high-quality 3D structures. CPXV (Protein A35, Protein Resolve A22, and Scaffold Protein) was selected for further analysis because of its varied immunological and physiochemical properties (Number of Amino Acids, Molecular Weight (Daltons), Theoretical pI Aliphatic index, Grand average of hydropathicity (GRAVY), Instability index GC content, and CAI value) and docking scores. The bacterial expression system showed notable gene expression for the CPXV-V5 vaccine, as shown by computational cloning analysis. Molecular dynamics (MD) simulations revealed structural stability and long-term epitope visibility, implying strong immune responses after delivery. These results suggest that the developed vaccines might be quite safe and effective in practical settings, and they offer a solid foundation for further experimental verification.